2011
DOI: 10.1042/cbi20100668
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial–mesenchymal transdifferentiation of renal tubular epithelial cells induced by urinary proteins requires the activation of PKC-α and βI isozymes

Abstract: Proteinuria is a common feature for almost all glomerular diseases and reflects the severity of the glomerular lesion. The presence of a large amount of proteins in tubular fluid, however, may also contribute to the development of RIF (renal interstitial fibrosis). Endocytosis of albumin in proximal tubular cells triggers PKC (protein kinase C)-dependent generation of reactive oxygen species and secretion of chemokines. As a family including 12 isozymes, which PKC isozymes participate in RIF is still unclear. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 25 publications
0
20
0
5
Order By: Relevance
“…Renal hypoxia induces epithelialmesenchymal trans-differentiation of the tubular cells and activates fibroblasts, which in turn plays a crucial role in the progression of renal interstitial fibrosis and damage of peritubular capillaries. 82,83 Trans-differentiated cells also stimulate the production of collagen I and α-smooth muscle actin. 79 As a result, tubular atrophy occurs and further impairment of oxygen supply is induced.…”
Section: Hypoxiamentioning
confidence: 99%
“…Renal hypoxia induces epithelialmesenchymal trans-differentiation of the tubular cells and activates fibroblasts, which in turn plays a crucial role in the progression of renal interstitial fibrosis and damage of peritubular capillaries. 82,83 Trans-differentiated cells also stimulate the production of collagen I and α-smooth muscle actin. 79 As a result, tubular atrophy occurs and further impairment of oxygen supply is induced.…”
Section: Hypoxiamentioning
confidence: 99%
“…RTEC suffering from EMT plays a crucial role in the progression of RIF. 16,17 α-Smooth muscle actin (α-SMA), as a specific marker for EMT, takes part in the development and progression of RIF. 16,18 Of all the cytokines and growth factors involved, transforming growth factor (TGF)-β1 plays the most important role, and the increased expression of TGF-β1 is closely correlated with the development of RIF.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 α-Smooth muscle actin (α-SMA), as a specific marker for EMT, takes part in the development and progression of RIF. 16,18 Of all the cytokines and growth factors involved, transforming growth factor (TGF)-β1 plays the most important role, and the increased expression of TGF-β1 is closely correlated with the development of RIF. 19,20 TGF-β1 is known to be one of the major mediators which leads to RIF by inducing the production of α-SMA and ECM (Col-IV and FN) in the renal interstitium.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that a high concentration of glucose and angiotensin II may promote EMT in kidney epithelial cells (16,17). The current study examined whether those substances would have the same effect on podocytes.…”
Section: A High Concentration Of Glucose and Angiotensin II Promoted mentioning
confidence: 97%